PARTITIONING OF TRACE ELEMENTS BETWEEN RUTILE AND SILICATE MELTS: IMPLICATIONS FOR SUBDUCTION ZONES - Klemme S.; Prowatke S.; Hametner K.; Günther D. (My University, 2005)
Mineral/melt trace element partition coefficients were determined for rutile (TiO2) for a large number of trace elements (Zr, Hf, Nb, Ta, V, Co, Cu, Zn, Sr, REE, Cr, Sb, W, U, Th). Whilst the high field strength elements (Zr, Hf, Nb, Ta) are compatible in rutile, other studied trace elements are incompatible (Sr, Th, REE). In all experiments we found DTa > DNb, DHf > DZr and DU > DTh. Partition coefficients for some polyvalent elements (Sb, W, and Co) were sensitive to oxygen fugacity. Melt composition exerts a strong influence on HFSE partition coefficients. With increasing polymerization of the melt, rutile/melt partition coefficients for the high field strength elements Zr, Hf, Nb and Ta increase about an order of magnitude. However, DNb/DTa and DHf/DZr are not significantly affected by melt composition. Because DU ≫ DTh, partial melting of rutile-bearing eclogite in subducted lithosphere may cause excesses of 230Th over 238U in some island arc lavas, whereas dehydration of subducted lithosphere may cause excesses of 238U over 230Th. From our partitioning results we infer partition coefficients for protactinium (Pa) which we predict to be much lower than previously anticipated. Contrary to previous studies, our data imply that rutile should not significantly influence observed 231Pa-235U disequilibria in certain volcanic rocks. Copyright © 2005 Elsevier Ltd.
Keywords: trace element partition; rutile; silicate melts